Reflecting on survivorship outcomes to aid initial decision making in patients treated for IDH‐mutated anaplastic glioma. Issue 19 (28th June 2019) - Back, Michael F.; Jayamanne, Dasantha; Back, Elizabeth; Kastelan, Marina; Khasraw, Mustafa; Wong, Matthew; Brown, Christopher; Wheeler, Helen
Abstract : Background: Patients with anaplastic glioma (AG) harboring an isocitrate dehydrogenase mutation have potential durable survival after intensity‐modulated radiotherapy (IMRT) and chemotherapy. Understanding long‐term functioning, and the factors that have an impact on later effects, is important for decision making. Methods: Consecutive patients with AG who received IMRT were reviewed with regard to 6 survivorship domains, including Eastern Cooperative Oncology Group (ECOG) performance status, Medical Research Council (MRC) neurological status, late toxicity, comorbidity, functional status (employment/driving), and psychosocial events. Assessments were performed at baseline before RT; at month +6; and at years +1, +3, and +5 after RT. The primary endpoints were ECOG at year +3 and employment at year +3. Results: A total of 146 patients were included, with a median follow‐up of 5.1 years. The 6‐year overall survival rate was 78.7% (95% CI, 71.1%‐87.0%). Baseline ECOG performance status was 0 to 1 in 82.2% of patients but improved at year +1 (95.7%) and year +3 (97.2%). Employment rates at year +3 and year +5 were 70.1% and 76.5%, respectively, compared with 61.6% at baseline. Worse ECOG performance status at year +3 was related to the anaplastic astrocytoma subtype ( P = .001), delayed RT ( P = .081), multiple craniotomies performed before RT ( P = .002), worse ECOG performance status before RT ( P < .001), worse MRC neurological status before RT ( P < .001), seizures ( P = .038), neurocognitive disturbance ( P < .001), and the presence of recurrent disease ( P = .004). Absent or impaired employment at year +3 was found to be related to older age ( P = .007), delayed timing of RT ( P = .023), multiple craniotomies prior to RT ( P = .005), worse ECOG performance status before RT ( P < .001), worse MRC neurological status before RT ( P < .001), and neurocognitive disturbance ( P < .001). Conclusions: Patients with AG with an isocitrate dehydrogenase mutation have the potential for prolonged survival. Functional status appears to be good in patients who are free of disease progression at 3 to 5 years after IMRT, with >95% of patients having high ECOG performance status and >75% being employed. Abstract : Patients with anaplastic glioma harboring the isocitrate dehydrogenase mutation have a long survival duration after the administration of intensity‐modulated radiotherapy and chemotherapy. Functional status at 3 years after treatment appears to be good, with >95% of patients having a high Eastern Cooperative Oncology Group performance status and >75% being employed.